2017
DOI: 10.1063/1.4997916
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic and induction effects in the solubility of water in alkanes

Abstract: Experiments show that at 298 K and 1 atm pressure the transfer free energy, µ ex , of water from its vapor to liquid normal alkanes CnH2n+2 (n = 5 . . . 12) is negative. Earlier it was found that with the united-atom TraPPE model for alkanes and the SPC/E model for water, one had to artificially enhance the attractive alkane-water cross interaction to capture this behavior. Here we revisit the calculation of µ ex using the polarizable AMOEBA and the non-polarizable Charmm General (CGenFF) forcefields. We test … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In contrast, the potential energy surfaces of the water–methane interactions described by the TIP4P/TraPPE–UA and SPC/E-1.7/TraPPE–UA combinations depend only on the oxygen–carbon distance (i.e., is invariant to changes in orientation) and yield binding energies of only 0.9 and 1.5 kJ/mol. This example illustrates the shortcomings of effective, nonpolarizable potentials (see also refs , , , , and ) but also indicates that these effective potentials should not strive to reproduce dimer energies.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In contrast, the potential energy surfaces of the water–methane interactions described by the TIP4P/TraPPE–UA and SPC/E-1.7/TraPPE–UA combinations depend only on the oxygen–carbon distance (i.e., is invariant to changes in orientation) and yield binding energies of only 0.9 and 1.5 kJ/mol. This example illustrates the shortcomings of effective, nonpolarizable potentials (see also refs , , , , and ) but also indicates that these effective potentials should not strive to reproduce dimer energies.…”
Section: Discussionmentioning
confidence: 71%
“…Clearly, the Lorentz− Berthelot combining rules are far from optimal when considering unlike interactions for atoms that differ greatly in the number of electrons (e.g., helium/xenon mixtures 35 ) but may also not be the most suitable choice for water−alkane mixtures due to the large difference in the well depths. 72 There is no doubt that more complex force fields (explicithydrogen representation of the alkanes, Gaussian partial charges to reflect the charge distribution of water 73 and alkanes, explicit accounting for many-body induction, 30,74,75 coupling between fluctuating partial charges and dispersive terms, 76 allowance for charge transfer, 76 and inclusion of nuclear quantum effects 77,78 ) can yield a more accurate description of water/alkane mixtures, but each of these complexities comes with a large increase in the computational expense that are multiplicative. Akin-Ojo and Szalewicz 79 have used high-level electronic structure theory to determine the potential energy surface for the water−methane dimer and obtained a rugged surface with two distinct minima with binding energies of 4.3 and 3.0 kJ/mol for configurations with methane as the hydrogen-bond acceptor and as the donor, respectively.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, from a PC-SAFT model and molecular dynamics simulations, the effective water Lennard–Jones energy was found much larger than that commonly used in simulation water models for describing the solubility of water in alkanes. This prompted the same research group to perform ab initio calculations, which revealed that nonpolar molecules, such as n -alkanes can be electrostatically induced by the presence of water molecules, consistent with other independent works. , They even conclude that the electrostatic and induction effects must be included to predict correctly the water content in alkanes …”
Section: Introductionmentioning
confidence: 99%